نحو تعزيز مشاركة اصحاب المصلحة في العملية التخطيطية العمرانية ( حالة دراسية : تجربة مدينة سنغافورة ) - ماهر لفّاح; سامي شيخ ديب; صفية حمودي (Tishreen University, 2016)
يلقي البحث الضوء على أهمية إشراك أصحاب المصلحة في عملية اتخاذ القرار التخطيطي العمراني لتلبية احتياجاتهم التي حددوها بالمشاركة ,كما يوضح المتطلبات اللازمة لضمان مشاركة فعالة لهم في إطار مقاربة تشاركية مناسبة تعتمد على رغبة سياسية لدى أصحاب القرار باعتماد تلك المقاربة والتوافقية بين الشركاء وممثليهم من جهة ,وبين المتطلبات والإمكانات من جهة أخرى .كما يعرف البحث بدرجات ومستويات مشاركة أصحاب المصلحة في العملية التخطيطية العمرانية من خلال عرض بعض النماذج والمصفوفات التي تعتمد في قياس مستويات المشاركة. يتناول البحث تجربة إعداد المخطط العام لمدينة سنغافورة كنموذج رائد عن مشاركة فعالة لأصحاب المصلحة في إعداد المخطط العام لمدينتهم موضحاً المنهجية المتبعة ضمن مراحل العملية التخطيطية العمرانية وأهم القضايا التي تم عنونتها بالمشاركة كموجهات لإعداد المخطط العام ضمن رؤية تحويل المدينة إلى مدينة عالمية وحيوية قادرة على مواجهة تحديات العولمة ومتطلبات الحياة المتسارعة ؛وتعمل على تطوير أفضل للبيئة ولنوعية حياة السكان ؛كما تحافظ على هوية المكان بمبانيه القديمة والحديثة ؛وتحافظ على مواقع الاستجمام في منطقة حضرية كبيرة  تعاني ندرة في الأراضي. يهدف البحث إلى تحديد المؤشرات الأساسية لتجربة مدينة سنغافورة وبيان مدى إمكانية تطبيقها في سورية لتفعيل مشاركة أصحاب المصلحة في العملية التخطيطية العمرانية. The paper sheds light on the importance of involving stakeholders in the decision-making process of urban planning to meet the needs they have identified in advance ,and the requirements to ensure the effective participation of stakeholders depending on the willingness of political decision-makers with the adoption of a participatory approach and interoperability between the partners and their representatives on the one hand and between the requirements and the capabilities on the other .The paper, moreover, shed lights on varying levels of stakeholders participation in the urban planning process through the presentation of some of the models and matrices that rely on measuring the levels of participation. The paper tackles the experience of preparing the general plan of Singapore city as a good model of an effective participation of stakeholders in the preparation of the general plan for their city, explaining the methodology used within the process of planning and construction which is the most important issues that have been labeled as a guidelines for the preparation of the general plan. In order to take advantage of the theoretical framework, practical examples in identifying obstacles in the application of a participatory approach in the Syrian Arab Republic were used in spite of the general trend towards the adoption of stakeholders participation.